Comparison of the effectiveness of butterfly arch versus transpalatal arch in anchorage reinforcement: A linear 3D finite element study - Nouf Bano; Sunil Kumar M; Prashantha Govinakovi Shivamurthy; Sharanya Sabrish; Silju Mathew (Tabriz University of Medical Sciences, 2022)
Background. Although there are various intraoral and extraoral appliances for anchorage management in orthodontics, most fail to preserve the anchorage efficiently. Thus, there is a need for an appliance that can preserve anchorage in the sagittal, vertical, and transverse directions with good patience compliance and cost-effectiveness. This study compared the efficacy of butterfly arch and transpalatal arch (TPA) as an anchorage reinforcing unit during orthodontic space closure using a linear finite element model. Methods. A 3D model of the maxilla and associated structures was developed from CT images of an individual's skull at a slice thickness of 1 mm. The magnitude of movements of anchor teeth in vertical, horizontal, and transverse directions was calculated in first premolar extraction cases during anterior retraction using a linear finite element model analysis and compared in two situations-butterfly arch and TPA attached to maxillary first molar for anchorage. Results. The anterior teeth had similar movements in the case of TPA and butterfly arch. There was more mesial and lingual movement in the first molars with TPA than in the butterfly arch, which had buccal but no mesial movement. The anterior teeth showed extrusion and the second premolars showed intrusion with TPA. Also, the von Mises stress and maximum principal stress were maximum with TPA at the cervical region of anterior and posterior teeth compared to the butterfly arch, where both stresses were uniformly distributed all over the teeth. Conclusion. A butterfly arch with its unique design, configuration, and biomechanical properties can be used as a device that can maintain the posterior anchorage efficiently